Eugenics. A historical analysis and a possible proposal - Villela Cortés, Fabiola; Linares Salgado, Jorge E. (Acta Bioethica, 2011)
Eugenics is a topic treated for several reasons by, among others, historians, philosophers, physicians, bioethicists. The idea to improve human race always has been present in the history of civilization, to try to consolidate it as a science also has been the object of commentaries, the presence of eugenic organizations in several countries, the nazi holocaust and finally, the eugenic resurgence since the human genome sequencing. Our objective is to review eugenic movements in the mid twentieth century, eugenic resurgence and current advancements.